2014
DOI: 10.1002/2014ja020005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of storm time magnetotail and ion injection using three‐dimensional global hybrid simulation

Abstract: 2014), Investigation of storm time magnetotail and ion injection using three-dimensional global hybrid simulation, Abstract Dynamics of the near-Earth magnetotail associated with substorms during a period of extended southward interplanetary magnetic field is studied using a three-dimensional (3-D) global hybrid simulation model that includes both the dayside and nightside magnetosphere, for the first time, with physics from the ion kinetic to the global Alfvénic convection scales. It is found that the dayside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
162
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(170 citation statements)
references
References 97 publications
(132 reference statements)
8
162
0
Order By: Relevance
“…Using a local two-fluid simulation of the current sheet, Ohtani et al (2004) shows multiple X points, of which one starts to dominate after reconnection spreads to the lobe field lines. Similar conclusions are made based on local kinetic simulations (Lapenta et al, 2015) and by global hybrid-PIC simulations (Lin et al, 2014). The earthward-moving multiple reconnection sites have been observed by, e.g., Eastwood et al (2005) using the Cluster spacecraft.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Using a local two-fluid simulation of the current sheet, Ohtani et al (2004) shows multiple X points, of which one starts to dominate after reconnection spreads to the lobe field lines. Similar conclusions are made based on local kinetic simulations (Lapenta et al, 2015) and by global hybrid-PIC simulations (Lin et al, 2014). The earthward-moving multiple reconnection sites have been observed by, e.g., Eastwood et al (2005) using the Cluster spacecraft.…”
Section: Discussionsupporting
confidence: 79%
“…Since the simulation is still 2-D at the moment, our results concern reconnection in a single meridional plane and cannot be generalised to concern multiple reconnection sites on a global 3-D current layer. Using a much coarser resolution, Lin et al (2014) found multiple X lines but that dominant X lines can form if they are not competing with other X lines on a similar meridional plane. Future versions of Vlasiator shall investigate whether this is also true in the hybrid-Vlasov approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain why spacecraft observations in Earth's magnetotail have shown electron currents to be much stronger than ion currents 6,39,54 . Similar results are found in numerical simulations 28,29 . An electric field E z can play an essential role in ion energization within thin current sheets located near the reconnection region.…”
Section: Discussionsupporting
confidence: 89%
“…In our previous study, 44 we investigated several important processes associated with substorms such as dipolarization, ballooning instability, and ion injection. In the present study, we mainly focus on the physics of the flux ropes and magnetotail reconnection.…”
Section: Introductionmentioning
confidence: 99%